FPGA-Based True Random Number Generation Using Programmable Delays in Oscillator-Rings (International Journal of Food and Nutritional Sciences, 2022)
True random number generators (TRNGs) are widely used in cryptographic applications such as key generation, random padding bits, and generation of challenges and nonces in authentication protocol. This paper proposes a new and efficient method to generate true random numbers in XILINX by utilizing the random jitter of free running oscillators as a source of randomness. The main advantage of the proposed true random number generator utilizing programmable delay lines is to reduce correlation between several equal length oscillator rings, and thus improve the randomness qualities. In addition, a Von Neumann corrector as post-processor is employed to remove any bias in the output bit sequence. clock gating architecture to limit the switching activity of the address decoder which improves the power efficiency of the proposed number generator. element structure is adapted to evaluate the clock cycle to the present ring counter block and to release the clock pulse to the next ring counter block. LUT memory accessing does not need write operations so data lines and read/write lines to the SRAM memory architecture is omitted.